MODEL PEMBELAJARAN INOVATIF MATEMATIKA PADA MAHASISWA - Rahmawati, Novia Dwi (JURNAL e-DuMath, 2016)
Nowadays, many education problem issues such monotonous class condition, students can get the education of sources in addition to campus, the change of economics condition influence behavior, and universities are expected to tackle the problems of education as more, and more parents busy working. Therefore, required renewal in learning, creating learning that is innovative, creative, and fun. The innovative learning model consist of problem based instruction, quantum teaching, cooperative learning, contextual teaching and learning and direct instruction. Keywords: the problem of education, innovative learning model